1999
DOI: 10.1143/jjap.38.2816
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Aging Effect in Poled Ferroelectric SrBi2(Ta,Nb)2O9 Capacitors

Abstract: Changes in the electrical properties of poled ferroelectric SrBi 2 (Ta,Nb) 2 O 9 (SBTN) thin-film capacitors caused by hightemperature storage were studied. Current-voltage (J-V) characteristics of SBTN capacitors before and after high-temperature storage indicated that the current in SBTN is predominantly carried by electrons and limited by electrode interfaces. The voltage shift in the polarization-voltage (P-V) curve caused at high temperatures was ascribed to a bulk effect because there were no definite ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Accordingly, the decrease in switching charge and the hysteresis shift due to imprint were investigated separately in order to discuss the mechanism underlying the imprint characteristics. [1][2][3][4] However, as we reported in a previous paper, 5) we found that the decrease in switching charge is accompanied by hysteresis shifts. Therefore, the measurement of the hysteresis shift was more important considering the origin of the imprint characteristics.…”
Section: Introductionmentioning
confidence: 68%
“…Accordingly, the decrease in switching charge and the hysteresis shift due to imprint were investigated separately in order to discuss the mechanism underlying the imprint characteristics. [1][2][3][4] However, as we reported in a previous paper, 5) we found that the decrease in switching charge is accompanied by hysteresis shifts. Therefore, the measurement of the hysteresis shift was more important considering the origin of the imprint characteristics.…”
Section: Introductionmentioning
confidence: 68%
“…Okazaki 1) first discussed the aging characteristics of bulk ferroelectric ceramics in detail and found that they were due to the space charge distribution. Recently, many authors have been investigating imprint characteristics and their origins in ferroelectric thin films, [2][3][4][5] but the parameters and the conditions for measuring these characteristics have not been standardized, and this fact has prevented the understanding of the origins. It was found that the hysteresis shifts are the most important parameters for understanding the imprint characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…FeRAM is widely researched to achieve higher density memory cells and lower voltage operation. Recently, improvement of the imprint property of a ferroelectric capacitor has become increasingly important for lower voltage FeRAM operation, and there are many reports concerning imprint behavior [1][2][3][4][5][6] and mechanism [7][8][9][10] and the improvement of imprint properties. [11][12][13] Pb(Zr,Ti)O 3 (PZT) is one of the strongest candidates for the ferroelectric material of future FeRAM because of features such as its large switching charge, ease of orientation control, and capability for a low-temperature process.…”
Section: Introductionmentioning
confidence: 99%